Some Remarks about Works Contracts in the Light of Supreme Court Case-Law - Karwowska, Aneta (Studia Oeconomica Posnaniensia, 2015)
Works contracts for construction belong to that category of legal structures in which the practical applications are dynamic and closely linked to the process of economic development. This publication aims to highlight some of the significant practical issues regarding the characteristics of works contracts and how to apply the relevant legal regulations and changes in case-law; primarily with regard to the interpretation of the individual provisions in the assessment of the author. This kind of agreement is defined by law as a named, mutual, paid, and consensual commitment to achieving a result. The economic aim of a building works contract is to complete the intended investment project.